Copper nano-architecture topical cream for the accelerated recovery of burnt skin. Issue 4 (1st February 2023) - Ermini, Maria Laura; Summa, Maria; Zamborlin, Agata; Frusca, Valentina; Mapanao, Ana Katrina; Mugnaioli, Enrico; Bertorelli, Rosalia; Voliani, Valerio
Abstract : This study demonstrates the potential of copper nanotechnology for the topical treatment of burn injuries and opens new horizons in oncological dermatology. Abstract : Skin burns are debilitating injuries with significant morbidity and mortality associated with infections and sepsis, particularly in immunocompromised patients. In this context, nanotechnology can provide pioneering approaches for the topical treatment of burnt skin. Herein, the significant recovery of radiation-damaged skin by exploiting copper ultrasmall-in-nano architectures (CuNAs) dispersed in a home-made cosmetic cream is described and compared to other noble metals (such as gold). Owing to their peculiar design and components, CuNAs elicit a substantial recovery from burned skin in in vivo models after one topical application, and a significant anti-inflammatory effect is highlighted by reducing cytokine expression. The treatment exhibited neither significant toxicity nor the alteration of copper metabolism in the target organs because of the CuNA biocompatibility. This study may open new horizons in the treatment of radiation dermatitis and skin burns caused by other external events.